Association between High On-Aspirin Platelet Reactivity and Reduced Superoxide Dismutase Activity in Patients Affected by Type 2 Diabetes Mellitus or Primary Hypercholesterolemia - Barale, Cristina; Cavalot, Franco; Frascaroli, Chiara; Bonomo, Katia; Morotti, Alessandro; Guerrasio, Angelo; Russo, Isabella (International journal of molecular sciences, 2020)
Platelet hyperactivation is involved in the established prothrombotic condition of metabolic diseases such as Type 2 Diabetes Mellitus (T2DM) and familial hypercholesterolemia (HC), justifying the therapy with aspirin, a suppressor of thromboxane synthesis through the irreversible inhibition of cyclooxygenase-1 (COX-1), to prevent cardiovascular diseases. However, some patients on aspirin show a higher than expected platelet reactivity due, at least in part, to a pro-oxidant milieu. The aim of this study was to investigate platelet reactivity in T2DM (n = 103) or HC (n = 61) patients (aspirin, 100 mg/day) and its correlation with biomarkers of redox function including the superoxide anion scavenger superoxide dismutase (SOD) and the in vivo marker of oxidative stress urinary 8-iso-prostaglandin F2α. As results, in T2DM and HC subjects the prevalence of high on-aspirin platelet reactivity was comparable when both non-COX-1-dependent and COX-1-dependent assays were performed, and platelet reactivity is associated with a lower SOD activity that in a stepwise linear regression appears as the only predictor of platelet reactivity. To conclude, in T2DM and HC, similarly, the impairment of redox equilibrium associated with a decrease of SOD activity could contribute to a suboptimal response to aspirin.